Accuracy of advanced deep learning with tensorflow and keras for classifying teeth developmental stages in digital panoramic imaging - Norhasmira, Mohammad; Anuar Mikdad, Muad; Rohana, Ahmad; Mohd Yusmiaidil, Putera Mohd Yusof (BioMed Central Ltd, 2022)
Background: This study aims to propose the combinations of image processing and machine learning model to segment the maturity development of the mandibular premolars using a Keras-based deep learning convolutional neural networks (DCNN) model. Methods: A dataset consisting of 240 images (20 images per stage per sex) of retrospect digital dental panoramic imaging of patients between 5 and 14 years of age was retrieved. In image preprocessing, abounding box with a dimension of 250×250 pixels was assigned to the left mandibular frst (P1) and second (P2) permanent premolars. The implementation of dynamic programming of active contour (DP-AC) and convolutions neural network on images that require the procedure of image fltration using Python TensorFlow and Keras libraries were performed in image segmentation and classifcation, respectively. Results: Image segmentation using the DP-AC algorithm enhanced the visibility of the image features in the region of interest while suppressing the image’s background noise. The proposed model has an accuracy of 97.74%, 96.63% and 78.13% on the training, validation, and testing set, respectively. In addition, moderate agreement (Kappa value=0.58) between human observer and computer were identifed. Nonetheless, a robust DCNN model was achieved as there is no sign of the model’s over-or under-ftting upon the learning process. Conclusions: The application of digital imaging and deep learning techniques used by the DP-AC and convolutions neural network algorithms to segment and identify premolars provides promising results for semi-automated forensic dental staging in the future